RIFM fragrance ingredient safety assessment, 1-(1, 2, 3, 4-tetrahydro-4, 4-dimethyl-1-naphthyl)propan-1-one, CAS Registry Number 74499-60-8. (November 2016) - Api, A.M.; Belsito, D.; Bhatia, S.; Bruze, M.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; Kromidas, L.; La Cava, S.; Lalko, J.F.; Lapczynski, A.; et al.
Abstract: The use of this material under current use conditions is supported by the existing information. This material was evaluated for genotoxicity, repeated dose toxicity, developmental and reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, as well as environmental safety. Data from the target material and the suitable read across analog 6-acetyl-1, 1, 2, 4, 4, 7-hexamethyltetraline (CAS # 21145-77-7) show that this material is not genotoxic. Data from the suitable read across analog 6-acetyl-1, 1, 2, 4, 4, 7-hexamethyltetraline (CAS # 21145-77-7) provided a MOE > 100 for the repeat dose and developmental toxicity endpoints. The reproductive and local respiratory toxicity endpoints were completed using the TTC (Threshold of Toxicological Concern) for a Cramer Class II material (0.009 mg/kg/day and 0.47 mg/day, respectively). Data on the target material showed that this material is below the non-reactive DST for skin sensitization and did not have the potential for phototoxicity or photoallergenicity. The environmental endpoint was completed as described in the RIFM Framework. Highlights: 1-(1, 2, 3, 4-Tetrahydro-4, 4-dimethyl-1-naphthyl)propan-1-one safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. All endpoints were cleared using data and/or read across data and/or TTC.